2021
DOI: 10.3390/ijms22179258
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Aryl Hydrocarbon Receptor Activating Environmental Pollutants on Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is an umbrella term that includes many different disorders that affect the development, communication, and behavior of an individual. Prevalence of ASD has risen exponentially in the past couple of decades. ASD has a complex etiology and traditionally recognized risk factors only account for a small percentage of incidence of the disorder. Recent studies have examined factors beyond the conventional risk factors (e.g., environmental pollution). There has been an increase in air p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 169 publications
0
6
0
Order By: Relevance
“…This differential effect may be attributed to the ability of PAHs to disrupt bone homeostasis through interactions between the aryl hydrocarbon receptor (AhR) and the receptor activator of nuclear factor kappa-B ligand (RANKL)-RANK complex [37]. This interaction can disturb bone homeostasis by activating various signaling pathways, including the nuclear factor kappa-B (NF-κB) pathway, the mitogen-activated protein kinase (MAPK) pathway, and the phosphoinositide 3-kinase (PI3K)/Akt pathway [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…This differential effect may be attributed to the ability of PAHs to disrupt bone homeostasis through interactions between the aryl hydrocarbon receptor (AhR) and the receptor activator of nuclear factor kappa-B ligand (RANKL)-RANK complex [37]. This interaction can disturb bone homeostasis by activating various signaling pathways, including the nuclear factor kappa-B (NF-κB) pathway, the mitogen-activated protein kinase (MAPK) pathway, and the phosphoinositide 3-kinase (PI3K)/Akt pathway [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…AhR is a ligand-activated transcription factor that regulates cell differentiation, proliferation, and cancer imitation. Therefore, activation of AhR is related to the pathogenesis of several diseases, such as cancer, cardiovascular disease, inflammatory diseases, atherosclerosis, and neurodegenerative diseases [ 191 ]. In adults, AhR is widely distributed and expressed in various tissues and regions of the brain [ 192 ].…”
Section: Perinatal Kp Metabolismmentioning
confidence: 99%
“…Placental physiology and placental gene expression are affected by several maternal factors, such as over and under-nutrition, drug and alcohol intake, smoking, a wide range of environmental toxicants, infections and stress [46,47]. Worth noting, a large array of environmental pollutants is activated by the aryl hydrocarbon receptor (AhR)/cytochrome P450 (CYPs) pathway, which in turn affects the epigenetic modulation of ASD-relevant genes [48]. Abruzzo et al (2019) reported a significant increase of the AhR signaling pathway in sera of ASD children [49].…”
Section: Non-linear Epigenetics and Paradigm Shift For Understanding ...mentioning
confidence: 99%